The expression of mothers in Facebook - Karalienė, Rasa (Information & Media, 2017)
In the digital age, a new global phenomenon of parents sharing the pictures of their children in social networks is observed in Lithuania as well. This raises the discussion on ethics, morality and safety issues when publicizing the images of children in social networks. The following issue is analyzed in the article: how mothers, who post their children’s images on Facebook, use their children for their own socializing needs. Not a lot of research regarding this issue has been done in Lithuania; consequently, this shows how unique the topic of this article is. The object of this article is the activity of mothers on Facebook. The purpose of this article is to indicate the peculiarities of how mothers express themselves when using images of their children in Facebook. Qualitative research was executed using the net-ethnographic strategy: the observation method was selected and an analysis scientific literature was done. The research allowed to evaluate the connection between the social behavior of mothers on Facebook with their personal features and to identify the characteristics of their self-expression by using the images of their children. The identified expression models were linked with personality types and sociocultural status. Though the social expression of every model has different elements of expression, the factor of the lack of responsibility for a child prevails in each of those models.